Employment and Household Welfare in Ghana - Bofah, R.O. (University of Ghana, 2019)
The developing world is challenged with a large number of persons involved in less productive and vulnerable employment. Ghana is not an exemption. This limits the country’s effort towards a successful achievement of the Sustainable Development Goals by 2030, particularly Goals 1, 8 and 10 which relate to ‘no poverty’, ‘decent work and economic growth’ and ‘lower inequality’, respectively. This study broadly examines the role of employment in explaining welfare in Ghana. To analyse this broad objective, the study carries out separate analyses to examine three specific research objectives and corresponding questions. The study contributes to the literature by analysing the effects of different groups of employment status on rural-urban household consumption welfare. Using data from the seventh round of the Ghana Living Standards Survey conducted in 2016/17 (GLSS7), the study finds higher returns to non-farm self-employed with employees (employers) than other forms of employment status. Non-farm self-employed without employees (own-account) and formal employees contribute to improving household welfare at the lower and more upper quantiles, respectively. Returns to non-farm own-account are found to be generally higher than agricultural own-account. The study finds detrimental effects of informal paid employment, unpaid employment, inactivity and unemployment on welfare. It shows clear consumption inequality gaps between rural and urban households, with the latter reporting a higher welfare at the mean and along all quantiles than the former. The observed inequality gaps are wider among the poorer than richer households. These gaps are primarily due to the differences in returns to observable characteristics between rural and urban households. Among others, employment, education and household size contribute most to explaining the observed rural-urban inequality gaps in Ghana. Also, the study contributes to the literature by examining the degree and determinants of employment diversification within and across the agricultural, services and industry sectors among rural households. Relying on data from the fifth and seventh rounds of the Ghana Living Standards Surveys conducted in 2005/06 and 2016/17 respectively (GLSS5 and GLSS7), the study reveals a greater degree of employment diversification within the agricultural sector followed by the services and industry sectors, respectively. Further, it is established that factors such as gender, marital status, education, landholdings, location, seasonal migration and infrastructural development remain key determinants of the on-going employment diversification in rural Ghana. For instance, being a female-head relative to being a male-head lowers employment diversification within the agricultural sector but increases diversification within the non-farm sectors (services and industry). In the same vein, infrastructural development in rural communities largely favours a higher degree of employment diversification within the non-farm sectors as compared to the agricultural sector. Another key finding is that education significantly decreases households’ diversification within the agricultural sector but increases that of the non-farm sectors. Further, the study contributes to the existing literature by examining the effect of employment diversification on the level of rural inequality and its change over time. Using the GLSS5 and GLSS7 datasets, the study establishes that the sum effect of employment diversification within the three major sectors contributes to decreasing the level of rural inequality in 2005/06 and 2016/17 and its change over the two periods while diversification across the sectors rather worsens rural inequality. The net effect of employment diversification is shown to be inequality-increasing. Regarding the independent effects of diversification within each of the three sectors, the agricultural and services sectors consistently contribute to reducing the level of and changes in rural inequality. Diversification within the industry sector worsens the change in inequality but marginally influences the level of inequality. A stimulating finding is that diversification within the agricultural sector contributes considerably to reducing the level of rural inequality than services and any other factor. In most cases, the effects of diversification are even much stronger when secondary employment activities are accounted for. The following recommendations are based on the study’s findings. To sustain and further enhance the welfare gains of non-farm employers, the government through its relevant institutions such as the Registrar General’s Department, the National Board for Small Scale Industries (NBSSI), the Ministry of Trade and Industry, the Ministry of Employment and Labour Relations and the Ministry of Business Development should expedite a nation-wide formalisation of the informal sector with emphasis on business registration, records keeping, customer service, innovation and basic management, among others. These actions are expected to improve and expand businesses owned by non-farm employers with the potential of generating employment and earnings opportunities for the unemployed, the unpaid worker, and the inactive, as well as other vulnerable workers including the agricultural own-account. Again, it is recommended that for rural households to experience a greater degree of employment diversification in the non-farm sectors, the government through its relevant institutions including the Electricity Company of Ghana, the Ghana Water Company, the Ministry of Roads, Highways and Transport, the Ministry of Trade and Industry, the Bank of Ghana and the National Development Planning Commission should prioritise infrastructural development across the rural communities. A particular attention should be geared towards the expansion or development of marketplaces, electricity, roads, portable water systems and financial institutions (such as banks and micro-finance) in the rural areas. Another policy direction is that government should aim at capitalising on the inequality-reducing effect of employment diversification within the services sector in rural Ghana. Key government institutions including the Ministry of Business Development, the Ministry of Trade and Industry, and the NBSSI should encourage, train and support rural farmers to complement their farming activities with wholesale and retail trading, and other forms of services. Furthermore, the observed negative linkage between employment diversification in the agricultural sector and education should be properly addressed through a specific policy intervention and public re-orientation. By encouraging educated persons into the agricultural sector, the country can minimise the socio-economic cost of the large numbers of unemployed secondary school leavers and tertiary graduates. In order to attract a good number of these leavers and graduates into the agricultural sector, the government, through its key stakeholders including the Ministry of Food and Agriculture, the Ministry of Business Development, the Ministry of Trade and Industry, the NBSSI, the ADB and the Ghana EXIM Bank, should aim at providing different forms of assistance such training, storage and credit facilities, and ready market in the sector. Such initiatives can improve the productivity of and returns to the agricultural sector and consequently minimise the present rural-urban consumption inequality gaps. By promoting a higher diversification in agricultural employment, the country stands a better chance of fighting against the rising rural inequality. Relatedly, government’s current initiatives on planting for food and jobs, rearing for food and jobs, one-village-one-dam and one-district-one-factory should, through the Ministry of Special Development Initiative, be used to stimulate employment opportunities across the rural areas with a particular attention on the savannah belt of the country. These policy initiatives should also aim at motivating and benefiting the unpaid workers, the unemployed and the inactive.
PhD. Development Economics
Keywords: Employment; Household; Welfare; Sustainable Development Goals (SDGS); Ghana